Экспедиционные исследования Кавказа (конец XIX в.) под руководством А. А. Иностранцева - (:unkn) unknown (My University, 2021)
Работа посвящена аналитическому обзору экспедиционных исследований (геологических и гидрологических), которые проводились на Кавказе под руководством А. А. Иностранцева в 90-е годы XIX в. Обобщены результаты геологических исследований конца XIX в., проводившихся в связи с инженерными работами по строительству железной дороги Владикавказ ― Тифлис. Рассмотрены результаты изысканий геологических партий, сформированных для трёх ключевых участков проводимой железнодорожной линии и тоннельных работ. За время проведения исследований был собран обширный фактический материал по геологии исследуемой территории, послуживший основой для развития петрографии. Показано, что кавказские геологические исследования сыграли заметную роль и оказали влияние на развитие геологии в России и мире. Отмечено, что гидрогеологические исследования под руководством А. А. Иностранцева позволили решить важный для региона вопрос водоснабжения.
Expeditional researches of the caucasus (late 19 th century) under the leadership of A. Inostrantsev
The work is devoted to an analytical review of expeditionary research (geological and hydrological), which were carried out in the Caucasus under the leadership of A. A. Inostrantsev in the 90s of the 19th century. The results of geological studies at the end of the 19th century, carried out in connection with engineering work on the construction of the Vladikavkaz ― Tiflis railway, are generalized. The results of surveys of geological parties formed for three key sections of the railway line and the upcoming tunneling works are considered. During the research, factual material was collected on the geology of the study area, which served for the development of petrography. It is shown that the Caucasian geological research has played a significant role and influenced the development of geology in Russia and the world. It is noted that hydrogeological research under the guidance of A. A. Inostrantsev helped to solve an important issue of water supply for the region.